Legal Assurance Analysis in Disputes Settlement of Rights Transfer to Land Due to Waqf - Kusuma Kusuma; Achmad Sulchan (Sultan Agung Notary Law Review, 2021)
The purpose of this research is to find out and analyze: 1). Implementation of the registration of the transfer of ownership of land due to waqf based on Ministerial Regulation no. 2 of 2017 in Madiun Regency. 2). Obstacles and solutions in the process of registering the transfer of ownership rights to land due to waqf. 3). Legal certainty in the settlement of disputes over the transfer of land due to waqf in Madiun Regency. The approach method in this research is empirical juridical, namely research that focuses on individual or community behavior in relation to the law. The data used are primary and secondary data obtained through interviews and literature study, while the data analysis method is done by qualitative descriptive analysis. The results of the research concluded: 1) Implementation of the registration of transfer of ownership rights to land due to waqf based on Ministerial Regulation no. 2 of 2017 in Madiun Regency, namely for land that has not been certified, the documents are equipped such as the Waqf Pledge Deed, photocopy of ID card/KK, photocopy of ID card/right owner identity, certificate of land history, statement of physical possession, power of attorney for application, photocopy of land and building tax, proof of title/proof of ownership, certificate of non-dispute and letter of approval of Nadzir, while for land registration that has been certified, the completeness of the documents required is the Deed of Waqf Pledge, certificate of land rights, photocopy of the applicant's ID card/KK Photocopy of the right owner's ID card/KK, application letter, statement of waqf grace period, Nazhir approval letter, statement of non-disputed land, a statement that the land/building is physically controlled, and proof of SSP/PPH. 2) Obstacles and solutions in the process of registering the transfer of ownership rights to land due to waqf in Madiun Regency, namely there are still some people who are still reluctant to take care of waqf land certificates, because of the assumption that the waqf land certification process requires very expensive costs, the solution made by the government is to carry out socialization and outreach activities to the community 3). Legal certainty in the settlement of disputes over the transfer of land due to waqf is based in Madiun Regency, namely if there is a dispute regarding the property that has been waqf, then the lawsuit is submitted to the competent Religious Court. However, the law allows the settlement of waqf disputes to be settled out of court, as described in Article 62 of Act No. 41 of 2004 concerning Waqf by prioritizing settlement through deliberation.